Interunit reliability of STATSports APEX global navigation satellite system and accelerometer-derived metrics during shuttle run protocols of varied distances and change of direction frequency - Dawson, L.; McErlain-Naylor, S. A.; Devereux, G.; Beato, M. (Journal of Sports Sciences, 2026)
This study assessed the interunit reliability of Global Navigation Satellite System (GNSS) and accelerometer-derived metrics during high-intensity shuttle run protocols. Thirty-three female football players completed three shuttle run protocols (2 × 20 m, 4 × 10 m, and 8 × 5 m). Two STATSports Apex Pro units (18 Hz GPS and 10 Hz Augmented GNSS; 100 Hz accelerometer) recorded accelerometer-derived (fatigue index [FI] and dynamic stress load [DSL]) and GNSS-derived (total distance, acceleration and deceleration counts, maximum speed, speed intensity and total metabolic power) metrics. Interunit reliability and agreement were evaluated using intraclass correlation coefficients (ICC), and Bland-Altman analysis. GNSS metrics demonstrated good to excellent reliability (ICC: 0.845-0.999), whereas accelerometer-derived metrics, FI (ICC: 0.495) and DSL (ICC: 0.484), showed poor reliability. Percentage bias in accelerometer-derived metrics ranged from -1.76% (FI) to -7.72% (DSL), and in GNSS metrics ranged from -0.1% (speed intensity) to 5.83% (decelerations), limits of agreement increased in protocols with more directional changes. Overall, the interunit reliability of accelerometer-derived metrics should be considered cautiously, especially in short, high-intensity activity. ICC and Bland-Altman analysis confirmed close agreement for the GNSS metrics but highlighted variability in accelerometer-derived metrics. Practitioners are advised to avoid interchanging units between athletes and sessions to maintain reliability.